CHILD AS A VICTIM OF DOMESTIC VIOLENCE - Karpuszenko, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Domestic violence is undoubtedly a topical yet still embarrassing problem of contemporary families.  Violence leaves an imprint on human mental health, thus negatively affecting the development and functioning of a child. The aim of this paper is to present views to various aspects of a child being a victim of domestic violence, at least from the standpoint of being the witness of violence of one parent against the other or experiencing physical or sexual abuse. This paper presents investigations of the violence against children and the analysis of selected problems discussed in the literature.